Curcumin-Loaded Chitosan Nanoparticle Preparation and Its Protective Effect on Celecoxib-induced Toxicity in Rat isolated Cardiomyocytes and Mitochondria - Ebrahimi, Hossein Ali; Esmaeli, Samira; Khezri, Saleh; Salimi, Ahmad (Drug Research, 2022)
Curcumin has a wide range of pharmacological activities, including antioxidant, anti-inflammatory and tissue protective. In here we hypothesized that curcumin-loaded chitosan-coated solid lipid nanoparticles (CuCsSLN) are able to increase its overall bioavailability and hence its antioxidant and mitochondria;/lysosomal protective properties of curcumin. CuCsSLN were prepared using solvent diffusion technique for formation of solid lipid nanoparticles (SLNs) and electrostatic coating of positive-charged chitosan to negative surface of SLNs. CuCsSLN showed the encapsulation efficiency of 91.4±2.7%, the mean particle size of 208±9 nm, the polydispersity index of 0.34±0.07, and the zeta potential of+53.5±3.7 mV. The scanning electron microscope (SEM) images of nanoparticles verified their nanometric size and also spherical shape. Curcumin was released from CuCsSLN in a sustain release pattern up to 24 hours. Then isolated cardiomyocytes and mitochondria were simultaneously treated with (1) control (0.05% ethanol), (2) celecoxib (20 µg/ml) treatment, (3) celecoxib (20 µg/ml)+++CuCsSLN (1 µg/ml) treatment, (4) CuCsSLN (1 µg/ml) treatment, (5) celecoxib (20 µg/ml)+++curcumin (10 µM) treatment and (6) curcumin (10 µM) treatment for 4 h at 37°C. The results showed that celecoxib (20 µg/ml) induced a significant increase in cytotoxicity, reactive oxygen species (ROS) formation, mitochondria membrane potential (ΔΨm) collapse, lipid peroxidation, oxidative stress and mitochondrial swelling while CuCsSLN and curcumin reverted the above toxic effect of celecoxib. Our data indicated that the effect of CuCsSLN in a number of experiments, is significantly better than that of curcumin which shows the role of chitosan nanoparticles in increasing effect of curcumin.
Keywords: nanotechnology; solid lipid nanoparticles; chitosan; celecoxib; curcumin; cardiotoxicity